Deep Brain Stimulation of the Habenula: Systematic Review of the Literature and Clinical Trial Registries - Germann, Jürgen; Mameli, Manuel; Elias, Gavin J. B.; Loh, Aaron; Taha, Alaa; Gouveia, Flavia Venetucci; Boutet, Alexandre; Lozano, Andres M. (Frontiers in Psychiatry, 2021)
The habenula is a small bilateral epithalamic structure that plays a key role in the regulation of the main monoaminergic systems. It is implicated in many aspects of behaviour such as reward processing, motivational behavior, behavioral adaptation, and sensory integration. A role of the habenula has been indicated in the pathophysiology of a number of neuropsychiatric disorders such as depression, addiction, obsessive-compulsive disorder, and bipolar disorder. Neuromodulation of the habenula using deep brain stimulation (DBS) as potential treatment has been proposed and a first successful case of habenula DBS was reported a decade ago. To provide an overview of the current state of habenula DBS in human subjects for the treatment of neuropsychiatric disorders we conducted a systematic review of both the published literature using PUBMED and current and past registered clinical trials using ClinicalTrials.gov as well as the International Clinical Trials Registry Platform. Using PRISMA guidelines five articles and five registered clinical trials were identified. The published articles detailed the results of habenula DBS for the treatment of schizophrenia, depression, obsessive-compulsive disorder, and bipolar disorder. Four are single case studies; one reports findings in two patients and positive clinical outcome is described in five of the six patients. Of the five registered clinical trials identified, four investigate habenula DBS for the treatment of depression and one for obsessive-compulsive disorder. One trial is listed as terminated, one is recruiting, two are not yet recruiting and the status of the fifth is unknown. The planned enrollment varies between 2 to 13 subjects and four of the five are open label trials. While the published studies suggest a potential role of habenula DBS for a number of indications, future trials and studies are necessary. The outcomes of the ongoing clinical trials will provide further valuable insights. Establishing habenula DBS, however, will depend on successful randomized clinical trials to confirm application and clinical benefit of this promising intervention.